Werbalna i pozawerbalna dyktatura „wrednych ludzi” w procesie komunikacji - Ślósarska, Joanna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
Presented topic includes following issues: 1) hidden dictatorship of the attitudes of ‘nasty people’ (‘diminishers’) and its influence on social relations; 2) strategies of depreciation that are used by ‘nasty people” (sowing incertitude, projections, generalizations, adjudications, psycho manipulations, hidden attacks, conflicting signals, provocations, creating illusory situations without exit); 3) verbal and extraverbal manifestations of the archetypes of ‘tormentor/victim’, ‘hunter/ hunted’, ‘attack/escape’ within the activity of ‘nasty people’; 4) long-term violation of the rules of symbolic interactionism by ‘diminishers’.In terms of methodological contexts there are taken mainly concepts of Jay Carter, Eric Berne, Herbert Blumer and Jean Baudrillard. Among historical contexts there is reference to the concept of neurotic personality (Freud, Horney) within the anthropological framework of seduction attitudes and communication play of evident/hidden. The analysis is proceeded on a set of artifacts that constitute oppressive ‘daily practices’.